Analisis Faktor-Faktor Yang Mempengaruhi Loyalitas Karyawan Pt Primissima (Persero) Yogyakarta - Affan, Junaidi; Putrikhrissa, Devita (Jurnal Solusi, 2019)
This study aims to obtain empirical evidence and examine the influence of leadership, compensation, work culture and work environment variables on the employee loyalty of PT Primissima Yogyakarta. Respondents in this study were permanent employees of PT Primissima, totaling 700 people with a sample of 88 people, data were analyzed using SPSS with multiple regression analysis methods with a significance level of 0.05. The analysis shows that partially or simultaneously leadership, compensation, work culture and work environment have a significant effect on employee loyalty. The contribution of leadership, compensation, work culture and work environment variables to employee loyalty is 69.5%